Bandwidth Widening of Piezoelectric Cantilever Beam Arrays by Mass-Tip Tuning for Low-Frequency Vibration Energy Harvesting - Eduard Dechant (Applied Sciences, 2017)
Wireless sensor networks usually rely on internal permanent or rechargeable batteries as a power supply, causing high maintenance efforts. An alternative solution is to supply the entire system by harvesting the ambient energy, for example, by transducing ambient vibrations into electric energy by virtue of the piezoelectric effect. The purpose of this paper is to present a simple engineering approach for the bandwidth optimization of vibration energy harvesting systems comprising multiple piezoelectric cantilevers (PECs). The frequency tuning of a particular cantilever is achieved by changing the tip mass. It is shown that the bandwidth enhancement by mass tuning is limited and requires several PECs with close resonance frequencies. At a fixed frequency detuning between subsequent PECs, the achievable bandwidth shows a saturation behavior as a function of the number of cantilevers used. Since the resonance frequency of each PEC is different, the output voltages at a particular excitation frequency have different amplitudes and phases. A simple power-transfer circuit where several PECs with an individual full wave bridge rectifier are connected in parallel allows one to extract the electrical power close to the theoretical maximum excluding the diode losses. The experiments performed on two- and three-PEC arrays show reasonable agreement with simulations and demonstrate that this power-transfer circuit additionally influences the frequency dependence of the harvested electrical power.